[Cu13{S2CNnBu2}6(acetylide)4]+: A Two‐Electron Superatom. Issue 47 (26th October 2016) - Chakrahari, Kiran Kumarvarma; Liao, Jian‐Hong; Kahlal, Samia; Liu, Yu‐Chiao; Chiang, Ming‐Hsi; Saillard, Jean‐Yves; Liu, C. W.
Abstract: The first structurally characterized copper cluster with a Cu13 centered cuboctahedral arrangement, a model of the bulk copper fcc structure, was observed in [Cu13 (S2 CN n Bu2 )6 (C≡CR)4 ](PF6 ) (R=C(O)OMe, C6 H4 F) nanoclusters. Four of the eight triangular faces of the cuboctahedron are capped by acetylide groups in μ3  fashion, and each of the six square faces is bridged by a dithiolate ligand in μ2, μ2 fashion, which leads to a truncated tetrahedron of twelve sulfur atoms. DFT calculations are fully consistent with the description of these Cu13 clusters as two‐electron superatoms, that is, a [Cu13 ] 11+ core passivated by ten monoanionic ligands, with an a1 HOMO containing two 1S jellium electrons. Abstract : Just like in the metal : Cu13 clusters with a centered cuboctahedral unit, a model of the bulk Cu metal fcc structure, have been synthesized. The [Cu13 ] 11+ core can be described as a two‐electron superatom; four of the eight triangular faces are capped by acetylide groups, and each of the six square faces is bridged by a dithiolate ligand to yield ideal tetrahedral symmetry.